2016
DOI: 10.1371/journal.ppat.1005811
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Protein Phosphatase PP2C38 Negatively Regulates the Central Immune Kinase BIK1

Abstract: Plants recognize pathogen-associated molecular patterns (PAMPs) via cell surface-localized pattern recognition receptors (PRRs), leading to PRR-triggered immunity (PTI). The Arabidopsis cytoplasmic kinase BIK1 is a downstream substrate of several PRR complexes. How plant PTI is negatively regulated is not fully understood. Here, we identify the protein phosphatase PP2C38 as a negative regulator of BIK1 activity and BIK1-mediated immunity. PP2C38 dynamically associates with BIK1, as well as with the PRRs FLS2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 70 publications
8
106
0
Order By: Relevance
“…Given the opposing phenotypes of the cpk28 and sik1 knockouts, CPK28 likely phosphorylates different BIK1 residues, resulting in an opposite effect on BIK1 protein turnover. BIK1 activity and abundance is regulated by multiple mechanisms (Couto et al, 2016; Liang et al, 2016; Monaghan et al, 2014), further highlighting its importance in plant immune signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Given the opposing phenotypes of the cpk28 and sik1 knockouts, CPK28 likely phosphorylates different BIK1 residues, resulting in an opposite effect on BIK1 protein turnover. BIK1 activity and abundance is regulated by multiple mechanisms (Couto et al, 2016; Liang et al, 2016; Monaghan et al, 2014), further highlighting its importance in plant immune signaling.…”
Section: Discussionmentioning
confidence: 99%
“…RLCKs are also subjected to layered regulations. A phosphatase PP2C38 negatively regulates PTI responses by modulating BIK1 phosphorylation and activity toward RBOHD (28). BIK1 is phosphorylated by CPK28, which likely leads to 26S proteasome-dependent BIK1 turnover at the resting state (114).…”
Section: Early Pattern Recognition Receptor Signaling Eventsmentioning
confidence: 99%
“…Upon flg22 treatment, PP2A activity has to be reduced to allow induction of BAK1 activity and PTI signaling [7]. Additionally, the PM-localized PP2C38 interacts with FLS2-BIK1 as well as EFR-BIK1 and dephosphorylates BIK1 to inhibit PAMP-induced ROS production and stomatal closure [8••]. Co-immunoprecipitation (Co-IP) experiments demonstrated that PP2C38 and BIK1 directly interact with each other.…”
Section: Phosphorylation Dynamics During Pathogen Perception and Pattmentioning
confidence: 99%
“…Co-immunoprecipitation (Co-IP) experiments demonstrated that PP2C38 and BIK1 directly interact with each other. A combined approach using genetics and phospho-proteomic analysis indicated that MAMP treatment induces BIK1-dependent phosphorylation of PP2C38 at Ser-77, which significantly diminishes the PP2C38 activity and its interaction with the receptor complexes [8••]. This interplay between immune regulatory kinases and phosphatases is a major mechanism by which plant cells achieve homeostasis during infection.…”
Section: Phosphorylation Dynamics During Pathogen Perception and Pattmentioning
confidence: 99%